There are apparently a huge number of correct answers ...
the statement of part-a that you've attached has so few
restrictions, requirements, or specifications.
∑ Hey, ramosblan81 ⊃
Answer:
x = -3
Step-by-step explanation:
<u><em>⇒ Given:</em></u>
<em>4x + 1 = 2x -5</em>
<em />
<u><em>║ Solve ║:</em></u>
<em>4x + 1 = 2x -5</em>
<em>Subtracting 1 from both sides:</em>
<em>4x + 1 = 2x -5</em>
<em>4x + 1 - 1 = 2x -5 -1</em>
<em>4x = 2x - 6</em>
<em>Now subtracting 2x from both sides:</em>
<em>4x - 2x = 2x - 6 - 2x</em>
<em>2x = -6</em>
<em>Then divide both sides by 2</em>
<em>2x/2 = -6/2</em>
<em>x = -3</em>
<em />
<em>Thus, the answer is x = -3.</em>
<em />
<u><em>xcookiex12</em></u>
<u><em></em></u>
<em>8/18/2022</em>
Answer:
x = - 4, x = 2
Step-by-step explanation:
Given
3x² + 6x - 24 = 0 ( divide through by 3 )
x² + 2x - 8 = 0 ← in standard form
(x + 4)(x - 2) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 4 = 0 ⇒ x = - 4
x - 2 = 0 ⇒ x = 2